(untitled) (International journal of artificial intelligence, 2025)
This artible discusses the modern aspects of education and healthcare systems. Development directions, their legal basis, existing problems and ways to eliminate them are analyzed. Also, the best practices of foreign countries in the education and healthcare systems are studied and the possibilities of adapting them to the national system are considered. The article pays special attention to the issues of access to education and medical services as priority areas of state policy.